Upaya Meningkatkan Hasil Belajar Peserta Didik dengan Menerapkan Model Pembelajaran Problem Based Learning di Kelas XI SMK Negeri 1 Pulau-Pulau Batu - Daratul Aini Gaho (Journal on Education, 2024)
This Classroom Action Research (PTK) was motivated by the low learning outcomes of students in mathematics education subjects. Therefore, this Classroom Action Research (PTK) aims to describe how to improve student learning outcomes by implementing the Problem Based Learning Model in Class XI of SMK Negeri 1 Pulau Batu Island. This type of research is Classroom Action Research (PTK) which consists of 2 cycles. The subjects in this classroom action research (PTK) were Class XI students at SMK Negeri 1 Pulau Batu Island with a total of 16 students. The results of the research showed that from the first cycle of students' learning test scores, it was clear that of the 16 students who were research subjects, there were 13 or 81% who got a score in the poor category, and 3 students or 19% who got a score in the good category. . This means that, after implementing the problem-based learning (PBL) model, the learning outcomes of class Therefore, researchers continued research in cycle II. The student learning outcomes obtained in cycle II were 16 students who were research subjects, showing that 100% of students achieved completeness with an average score of 85.6. This shows that the application of the problem-based learning (PBL) model with the improvements made after implementing cycle I has increased and has achieved classical completeness. In this case, the problem-based learning model can improve student learning outcomes in mathematics learning on the subject of matrix addition and subtraction operations and material on arithmetic sequences and series in class XI SMK Negeri 2 Pulau-Pulau Batu.